Effect of NPK on Vegetative Growth and Yield of Desiree and Kufri Sindhuri Potato - Adhikari, Ram C. (Nepal Agriculture Research Journal, 2014)
A field experiment was carried out to assess the effect of NPK on vegetative growth and yield of potato cultivars; Kufri Sindhuri and Desiree at different nutrient levels (0:0:0, 50:50:50, 100:50:50, 100:75:50, 100:75:100, 100:100:100 and 150:100:100 N, P205 and k20 kg ha-1) in sandy loam soils at Rampur, Chitwan, Nepal during 1999/2000. The experiment was laid out in a split plot design with 4 replications. Plant height, number of stems, fresh weight of stem and leaves were recorded at 15 days interval during crop growth period and tuber yield at maturity stage. Kufri Sindhuri was taller than Desiree at all the stages of plant growth. Increasing levels of NPK increased the plant height by 15-42 percent. The levels of NPK imparted to a significant effect on fresh weight of leaves and stems at each successive stages of crop growth. Kufri Sindhuri responded nitrogen up to 150 kg ha-1 while Desiree yielded higher at 100:100:100 kg NPK ha-1. The yield increase of potato tuber was associated with increase in the plant height, fresh weight of leaves and stems as a result of applied NPK. Nepal Agric. Res. J. Vol. 9, 2009, pp. 67-75 DOI: http://dx.doi.org/10.3126/narj.v9i0.11643